ChemInform Abstract: Desulfitative C‐Arylation of Glycals by Using Benzenesulfonyl Chlorides. Issue 22 (15th May 2015) - Kusunuru, Anil Kumar; Yousuf, Syed Khalid; Tatina, Madhubabu; Mukherjee, Debaraj
Abstract: The stereochemistry of this arylation reaction is controlled by the configuration at C3 of the glycal.